Improved sleep quality in older adults with insomnia reduces biomarkers of disease risk: Pilot results from a randomized controlled comparative efficacy trial. (May 2015) - Carroll, Judith E.; Seeman, Teresa E.; Olmstead, Richard; Melendez, Gerson; Sadakane, Ryan; Bootzin, Richard; Nicassio, Perry; Irwin, Michael R.
Highlights: Individuals starting the trial with high multisystem biological risk and assigned to CBT or TCC showed improvements in risk scores after 1 year. Findings suggest that improving sleep quality has the potential to reduce the risk of chronic disease in older adults with sleep disturbances. This is the first study to report that a treatment trial for insomnia in older adults impacts clinical markers of risk for disease. Summary: Importance: Sleep disturbances have been linked to increased morbidity and mortality, yet it is unknown whether improving sleep quality in older adult patients with insomnia alters biomarkers of diabetes and cardiovascular disease risk. Objective: Determine the comparative efficacy of cognitive behavioral therapy (CBT), tai chi chih (TCC), and a sleep seminar control (SS) to reduce multisystem biomarkers of disease risk in older adults with insomnia. Design: Randomized controlled comparative efficacy trial. Setting: Los Angeles community. Participants: A population-based sample of 109 older adults with chronic and primary insomnia. Intervention: Random assignment to CBT, TCC, or SS for 2-h group sessions weekly over 4 months with a 16-month evaluation (1 year after follow-up). Main outcome(s) and measure(s): Multisystem biological risk comprised of 8 biomarkers: high-density lipoprotein, low-density lipoprotein, triglycerides, hemoglobinA1c, glucose, insulin, C-reactive protein, and fibrinogen. Using clinical laboratory cutoffs defined as abnormal, a multisystem risk score was computed representing a sum of the deviation around the cutoffs across the 8 biomarkers. In addition, high risk grouping was classified if subjects exhibited 4 or more biomarkers in the abnormal laboratory range. Results: An interaction of time-by-treatment-by-high risk group was found ( F (4, 197.2) = 3.14, p = .02) in which both TCC ( p = .04) and CBT ( p = .001) showed significantly lower risk scores as compared to SS at 16-months. CBT reduced risk of being in the high risk group at 4-months (odds ratio [OR] = .21 [95% CI, .03–1.47], p < .10) and at 16-months (OR = .06 [95% CI, .005–.669]; p < .01). TCC reduced the risk at 16-months (OR = .10 [95% CI, .008–1.29]; p < .05) but not at 4 months. Of participants who were classified in the high risk category at baseline, improvements in sleep quality, as defined by a clinical severity threshold, reduced the likelihood of being in the high risk group at 16-months, OR = .08 (95% CI, .008–.78); p = .01. Conclusions and relevance: Participants classified as having high multisystem biological risk at entry and assigned to CBT or TCC show improvements in risk scores after one year follow-up. Given that these clinical biomarkers are associated with cardiovascular, metabolic, and inflammatory disease risk, improving sleep quality has the potential to reduce the risk of chronic disease in older adults with insomnia.